2001
DOI: 10.1046/j.1440-1819.2001.00800.x
|View full text |Cite
|
Sign up to set email alerts
|

Borderline personality traits in hysterical neurosis

Abstract: The objective of the present study is to demonstrate the traits of the psychopathology of Borderline Personality Disorder (BPD) compared with hysterical neurosis. A total of 48 subjects with BPD and 40 subjects with hysterical neurosis both defined by DSM-III-R were assessed by Diagnostic Interview for Borderlines (DIB). Statistical analysis was done by quantification of the second type, a multivariate data analysis. The total scores of DIB were BPD group, 6.13 ± 1.52; hysterical neurosis group, 4.9 ± 2.12 (t … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Intolerance of aloneness broadly relates to the intolerable distress of being alone with one's own thoughts and feelings and an associated incapacity for solitude [132]. Overall findings indicate that people with BPD experience the feeling of aloneness more frequently and severely compared individuals with neurotic disorders [113] and have an intolerance to being alone [61,105]. A recent study developed a measure for the experience of being alone for individuals with BPD and they report the intolerance of this experience as a salient feature of the disorder [132].…”
Section: Similar Constructsmentioning
confidence: 92%
See 1 more Smart Citation
“…Intolerance of aloneness broadly relates to the intolerable distress of being alone with one's own thoughts and feelings and an associated incapacity for solitude [132]. Overall findings indicate that people with BPD experience the feeling of aloneness more frequently and severely compared individuals with neurotic disorders [113] and have an intolerance to being alone [61,105]. A recent study developed a measure for the experience of being alone for individuals with BPD and they report the intolerance of this experience as a salient feature of the disorder [132].…”
Section: Similar Constructsmentioning
confidence: 92%
“…People with BPD demonstrated higher dysregulation compared to healthy controls following presentation of attachment pictures which may induce loneliness, suggesting an intolerance of loneliness [54]. Similarly, people with BPD demonstrated a higher intolerance to loneliness compared to people with dissociative or conversion disorders [105]. One study reported that loneliness in BPD was related to poor social and relational function, but after controlling for these deficits loneliness was still high for people with BPD, suggesting there are multiple factors which contribute to feeling lonely [89].…”
Section: Similar Constructsmentioning
confidence: 95%
“…Kluger and Song (2003) report similar dynamics between patients with BPD and their mental health practitioners and other service providers, which often become turbulent and strained, thereby demonstrating their global tendency to form intensely fragile attachments (Bateman & Fonagy, 2004). Patients with BPD, according to Ohshima (2001) are more demanding and manipulative, and have poorer and more conflicted relationships with medical personnel than non-BPD patients.…”
Section: Borderline Personality Disordermentioning
confidence: 99%